Gender-specific predictors of generalized anxiety disorder symptoms in older adults: results of a large population-based study - Böhlen, Friederike; Herzog, Wolfgang; Schellberg, Dieter; Maatouk, Imad; Schöttker, Ben; Brenner, Hermann; Wild, Beate (Journal of affective disorders, 2020)
Background: Anxiety in older age is common. In comparison with men, older women experience higher levels of anxiety and show different patterns of co-occurring mental disorders. The aim of this study is to investigate gender-specific biopsychosocial predictors associated with GAD (Generalized Anxiety Disorder) symptoms after a period of three years in the elderly population. Methods: Data were derived from the third (2008-2010) and the fourth follow-up (2011-2014) of the large population-based German ESTHER study. 2254 participants ages 55-85 were included in the study (52.3% female; 47.7% male). Generalized Anxiety Disorder Symptoms were measured using the GAD-7 questionnaire at both follow-ups. Linear regression analyses were performed to predict GAD severity after three years; the analyses were separated by gender and adjusted for demographic variables, biopsychosocial health, cognitive impairment, loneliness, and psychosocial resources. Results: In women, GAD severity after three years (t1) was positively associated with younger age, depression symptoms, loneliness, and GAD severity at t0. In men, GAD severity was positively associated with somatic symptoms as well as with GAD severity at t0. In both genders GAD severity at baseline was the strongest predictor of elevated future anxiety symptoms. Limitations: GAD was examined by the use of questionnaires rather than by personal assessment; underreporting of GAD symptoms is therefore possible. Conclusions: Our study shows that an increase as well as a decrease of GAD severity in older women and men can be predicted by several biopsychosocial variables.
Gesehen am 13.02.2020
Available online 19 October 2019